Modifying beliefs about back pain: A pilot study among healthcare professionals. Issue 4 (April 2016) - Monnin, Dominique; Courvoisier, Delphine S.; Genevay, Stéphane
Highlights: 101 employees followed the education program. Our intervention was based on promoting empowerment and problem-solving strategies. Back beliefs were less negative and fear-avoidance decreased after the intervention. Effect was maintained 6 months after the intervention. Abstract: Objectives: This study aimed to explore whether a preventive intervention based on the non-injury model and the biopsychosocial model of back pain succeeded in shifting beliefs toward less negative representations and in decreasing fear-avoidance beliefs related to back pain. Methods: One hundred and one healthcare professionals took part in a 10-h educational program held over 2 consecutive days, based on the key messages of the "Back Book." Baseline values were measured 6 weeks before the intervention and when it started. Follow-up was performed at the end of the intervention and six months later. Results: No significant changes were observed between baseline values and values measured at the beginning of the intervention, but participants' beliefs about LBP changed significantly after the program. The benefit remained at 6 months follow-up. Conclusion: A prevention program based on the non-injury and bio-psychosocial models of LBP, introducing empowerment and problem-solving strategies, significantly reduced fear-avoidance and negative beliefs about LBP. The change was clinically relevant and thus could decrease direct and indirect healthcare costs.